Ethnomedicinal wisdom of tribals of Mahur forest of Nanded district, Maharashtra, India. - Kanthale, P R; Biradar, S D (Recent Research in Science and Technology, 2013)
Mahur range forest of Nanded district is rich in medicinal plants. In the present paper 25 plants species belonging to 25 genera and 20 families used in folk medicine has been documented. Due to poor condition of modern healthcare facilities and poverty the tribal people and rustics of the forest fully or partially depend on local medicinal plants. An attempt has been made to document traditional knowledge from tribal people, medicinal practitioner, traditional healers medicinemen, herbal venders, rustics etc. The plants were enumerated alphabetically along with botanical name, family and vernacular name.